2005
DOI: 10.1098/rstb.2005.1771
|View full text |Cite
|
Sign up to set email alerts
|

Normal brain ageing: models and mechanisms

Abstract: Normal ageing is associated with a degree of decline in a number of cognitive functions. Apart from the issues raised by the current attempts to expand the lifespan, understanding the mechanisms and the detailed metabolic interactions involved in the process of normal neuronal ageing continues to be a challenge. One model, supported by a significant amount of experimental evidence, views the cellular ageing as a metabolic state characterized by an altered function of the metabolic triad: mitochondria-reactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 69 publications
(91 reference statements)
2
62
0
1
Order By: Relevance
“…This is increased in normal ageing [46]. Ca 2+ imaging studies have shown that the resting Ca 2+ concentration in CA 1 hippocampal neurons does not change with ageing, but that these cells show a greater rise in Ca 2+ in response to stimulation [56].…”
Section: Calcium Dysregulationmentioning
confidence: 98%
See 1 more Smart Citation
“…This is increased in normal ageing [46]. Ca 2+ imaging studies have shown that the resting Ca 2+ concentration in CA 1 hippocampal neurons does not change with ageing, but that these cells show a greater rise in Ca 2+ in response to stimulation [56].…”
Section: Calcium Dysregulationmentioning
confidence: 98%
“…Cellular and molecular changes in brain ageing have been well reviewed recently [44][45][46]. Here we consider some of the more important factors.…”
Section: Cellular and Molecular Changesmentioning
confidence: 99%
“…The role of oxygen radicals and ROS in neurodegeneration and cognitive decline has been demonstrated previously [18][19][20]. The age-related increase in oxidative brain damage is well exemplified by products of lipid peroxidation, protein oxidation and oxidative modifications in nuclear and mithocondrial DNA [21].…”
mentioning
confidence: 99%
“…3) Normal aging is not associated with widespread neuronal loss, but becomes increasingly vulnerable to the effects of excessive metabolic loads, usually associated with trauma, ischemia or neurodegenerative process. 4) Neurological diseases such as ischemia and dementia increase with aging. In both acute and chronic neurological diseases, glutamate excitotoxicity via excess of extracellular glutamate concentration is involved in neuronal damage.…”
Section: Introductionmentioning
confidence: 99%